Defects and disorder in metal organic frameworks. Issue 10 (2nd February 2016) - Cheetham, Anthony K.; Bennett, Thomas D.; Coudert, François-Xavier; Goodwin, Andrew L.
Abstract : The wide-ranging properties of metal organic frameworks (MOFs) rely in many cases on the presence of defects within their structures and the disorder that is inevitably associated with such defects. Abstract : The wide-ranging properties of metal organic frameworks (MOFs) rely in many cases on the presence of defects within their structures and the disorder that is inevitably associated with such defects. In the present work we review several aspects of defects in MOFs, ranging from simple substitutional defects at metal cation or ligand positions, to correlated defects on a larger length scale and the extreme case of disorder associated with amorphous MOFs. We consider both porous and dense MOFs, and focus particularly on the way in which defects and disorder can be used to tune physical properties such as gas adsorption, catalysis, photoluminescence, and electronic and mechanical properties.